Assessing leg blood flow and cardiac output during running using thermodilution - Leahy, M. G.; Thompson, K. M. A.; Skattebo, Ø.; de Paz, J. A.; Martin-Rincon, M.; Garcia-Gonzalez, E.; Galvan-Alvarez, V.; Boushel, R.; Hallén, J.; Burr, J. F.; Calbet, J. A. L. (Scandinavian Journal of Medicine & Science in Sports, 2024)
Cardiac output (QC) and leg blood flow (QLEG) can be measured simultaneously with high accuracy using transpulmonary and femoral vein thermodilution with a single-bolus injection. The invasive measure has offered important insight into leg hemodynamics and blood flow distribution during exercise. Despite being the natural modality of exercise in humans, there has been no direct measure of QLEG while running in humans. We sought to determine the feasibility of the thermodilution technique for measuring QLEG and conductance during high-intensity running, in an exploratory case study. A trained runner (30 years male) completed two maximal incremental tests on a cycle ergometer and motorized treadmill. QLEG and QC were determined using the single-bolus thermodilution technique. Arterial and venous blood were sampled throughout exercise, with continuous monitoring of metabolism, intra-arterial and venous pressure, and temperature. The participant reached a greater peak oxygen uptake (VO2peak) during running relative to cycling (74 vs. 68 mL/kg/min) with comparable QLEG (19.0 vs. 19.5 L/min) and QC (27.4 vs. 26.2 L/min). Leg vascular conductance was greater during high-intensity running relative to cycling (82 vs. 70 mL/min/mmHg @ ~80% VO2peak). The "beat phenomenon" was apparent in femoral flow while running, producing large gradients in conductance (62-90 mL/min/mmHg @ 70% VO2peak). In summary, we present the first direct measure of Q?LEG and conductance in a running human. Our findings corroborate several assumptions about QLEG during running compared with cycling. Importantly, we demonstrate that using thermodilution in running exercise can be completed effectively and safely.